Menumbuhkan Kepedulian Sosial Dan Kerjasama Anak Melalui Metode Groupwork - Viona Rosalinda Sembiring; Emi Triani; Fajar Utama Ritonga (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
Humans are social creatures who cannot live alone and need the help of others in every aspect of their lives. Good cooperation must be instilled in children from an early age so that they can develop and be able to function socially well in the future. Fostering social care and cooperation in children can be done in various ways even through games. Through games children are easier to learn. This activity was carried out as one of the mini projects of Field Work Practice 2 activities carried out at SOS Children's Villages Medan for the Family Strengthening Program. This activity was carried out at the Kwala Bekala Community. This Field Work Practice activity was carried out at the Kwala Bekala Community. This Field Work Practice activity was carried out for approximately 3 months. The method used in this study is the Groupwork method with general stages (1) Preparation, (2) Assessment, (3) Alternative Program Planning, (4) Action Plan Formulation, (5) Program Implementation, (6) Evaluation and Results of Change and (7) Termination.